Valproic Acid induced Acute Hemorrhagic Pancreatitis with Transient Hyperglycemia in a Child with Temporal Lobe Epilepsy: A Case Report: Valproic Acid induced Acute Hemorrhagic Pancreatitis (Journal of the Medical College for Women & Hospital, 2024)
Valproic acid (VPA) is a well-tolerated anti-epileptic drug. It is mainly used for the management of epilepsy, acute mania, bipolar mood disorder, and prophylactic treatment of migraine. Acute pancreatitis is a serious side effect of VPA with an incidence of 1:40,000. A higher number of cases has been reported among children and adolescents. The idiosyncratic reaction is the main cause of pancreatitis; however, a higher dose may aggravate the condition. In most cases, it usually develops on average 11 months afterVPA initiation; however, it is rarely seen before 3 months. Here we are reporting a 6-year-old boy who developed acute hemorrhagic pancreatitis within three months following initiation of VPA for management of temporal lobe epilepsy. The patient was successfully managed by conservative treatment with intensive care support. Finally, we discharged the patient with Levetiracetam and followed up without any side effects or any new episodes of seizure.J Med Coll Women Hosp. 2024; 20(2): 72-75